(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
North Macedonia is part of the Western Balkans. It is a transit route for migrants who want to reach the countries of the European Union. Macedonia is not their final destination, but it is a transit country, and part of the Balkan route. An asylum seeker is a foreigner who seeks protection from the state protection from the state and applying for asylum, and illegal migration is crossing the borders of states contrary to the conditions of legal admission to the state of reception. Illegal migration is a phenomenon that requires regional co-operation. Illegal migration is a serious sociological, cultural and social phenomenon of the criminological problem that has experienced enlargement in the last decade and which can be viewed from various aspects: security, criminology crime, psychological, moral, victimial, etc. The biggest challenge is the collapse of illegal migration, first because migrants immediately violate the order and we were also witness of physical attacks by members of the security forces that secure the borde.Other challenges of illegal migration include: health risks, endangering the lives of migrants, property delinquencies on migrants, becoming victims of trafficking, threatening national security, public order violations, migrant crime against the population, violation of human rights and many more that we will process in the paper. One of the major risks is that through illegal migration is the migration of terrorists who are the ultimate destination and plan for terrorist attacks are the countries of the European The large number of migrants who illegally crossed the border of Macedonia is due to criminal groups who transfer and accommodate them for financial compensation.